The Influence of Financial Literacy and Lifestyle on Financial Behavior of Generation Z in Makassar City in 2024 - Anwar Ramli; Annisa Paramaswary Aslam; Indah Lestari Anwar (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the influence of financial literacy on financial behavior and the influence of financial literacy on financial behavior with lifestyle as a moderating variable in generation Z in Makassar City in 2024. This research method uses a descriptive quantitative approach, which aims to analyze the influence of financial literacy and lifestyle on the financial behavior of generation Z in Makassar City in 2024. The variables analyzed are Financial Literacy, Lifestyle, and Financial Behavior. The data used in this study are primary data in the form of questionnaires and secondary data in the form of financial data. The population in this study is all generation Z in Makassar City. The sample of this study is generation Z in Makassar City with an age range of 18-27 years. The results of the study indicate that Financial Literacy has a significant influence on Financial Behavior in Generation Z in Makassar City. Thus, it is expected to provide practical recommendations for generation Z in managing finances and assist local government policies in improving financial literacy among youth. In addition, this research will be published in the form of a Sinta-accredited national journal to provide deeper insight into how financial literacy and lifestyle influence the financial behavior of Generation Z in Makassar.